1989
DOI: 10.1523/jneurosci.09-02-00565.1989
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor-like molecules in the retina, retinotectal pathway, and optic tectum of the frog

Abstract: Forty-two monoclonal antibodies (mAbs) generated against nicotinic acetylcholine receptors (AChRs) from electric organ were tested for their ability to cross-react in the optic tectum of the frog Rana pipiens. Twenty-eight of the mAbs tested (67%) bound to the optic neuropil of the tectum as revealed by immunoperoxidase cytochemistry. The pattern of peroxidase stain for cross-reacting mAbs corresponded in position to a subset of the retinotectal projections. Electron microscopic examination revealed that perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 50 publications
9
73
1
Order By: Relevance
“…Nicotinic receptors have been generally regarded as having a presynaptic location in the optic tectum following their immunocytochemical identification on retinal ganglion cell terminals (Sargent et al, 1989). More recent work in Xenopus has provided physiological evidence for this terminal location by showing that activation of nicotinic receptors increases sPSCs recorded in patch-clamped tectal cells (Titmus et al, 1999).…”
Section: Nicotinic Receptor Location In the Optic Tectummentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinic receptors have been generally regarded as having a presynaptic location in the optic tectum following their immunocytochemical identification on retinal ganglion cell terminals (Sargent et al, 1989). More recent work in Xenopus has provided physiological evidence for this terminal location by showing that activation of nicotinic receptors increases sPSCs recorded in patch-clamped tectal cells (Titmus et al, 1999).…”
Section: Nicotinic Receptor Location In the Optic Tectummentioning
confidence: 99%
“…The optic tectum of the frog contains both nicotinic and muscarinic cholinergic receptors (Sargent et al, 1989;Birdsall et al, 1980;Butt et al, 2000Butt et al, , 2001) but knowledge of the physiological consequences of their activation is incomplete. Assessments of the effects of nicotinic receptor activation have focused on a facilitation of glutamate release from retinal ganglion cell terminals (Titmus et al, 1999;Kuras and Gutmaniene, 2001) while muscarinic receptors have been associated with tectal cell membranes following an enhancement of single unit recordings in response to ACh microiontophoresis (Fite and Wang, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ␣7-nAChR mRNA and protein levels are markedly reduced after deafferentation of the rodent somatosensory cortex by lesioning of the thalamocortical inputs (Broides et al, 1996). Disruption of retinal inputs reduces nAChR ␣5, ␤2, and ␣7 subunit protein levels in the chick optic tectum neuropil (Britto et al, 1994;Torrao et al, 1996), and decreases binding of the nAChR ligands ␣-bgt and cytosine in the frog tectum (Sargent et al, 1989;Butt et al, 2000). These studies are complicated by the fact that nAChRs are expressed on both innervating presynaptic terminals and postsynaptic neurons found in the tectal neuropil, raising the possibility that degeneration of the lesioned nerve contributes to the loss of nAChR expression following denervation (Sargent et al, 1989;Torrao et al, 1996;Butt et al, 2000;Britto et al, 2001).…”
Section: Maintenance Of Nachr Expression Requires Innervationmentioning
confidence: 99%
“…Optic nerve lesions cause the degeneration of retinal ganglion cell terminals in the tectum and the disappearance of elements associated with them. 49,60,70 Optic nerve lesions had no significant effect on specific [ 3 H]pirenzepine binding in the tectum (Fig. 7A, B).…”
Section: Effect Of Optic Nerve Lesions On [ 3 H]pirenzepine and [ 3 Hmentioning
confidence: 91%
“…Earlier studies have shown that most retinal fibers in the tectum have degenerated after short-term lesions, but long-term lesions allow for the degeneration of all presynaptic retinal fibers. 49,60,70 Behavioral tests were conducted during the survival period to demonstrate that animals responded only to prey seen through the unlesioned left eye. At the end of the survival period, the frogs were anesthetized, the optic nerve lesion was confirmed and the brain was prepared for autoradiography as described above.…”
Section: Pharmacology Of Muscarinic Binding In the Optic Tectum-autormentioning
confidence: 99%